An Overview of Student Flow in Participating in HIMAPSI Organizational Activities Amidst Academic Demands - Shafyah, Shafyah Azmi; Putri Raudhatus Syifa; Nadya Tarisha Ginting; Tri Tsania Ambarwaty; Vebriana Misdar (Jurnal Psikologi Terapan, 2025)
This study aims to describe the flow experience of students who are active in the Psychology Student Association (HIMAPSI) at Malikussaleh University, amidst the academic pressures they face. Using a descriptive quantitative approach, 50 students became the subjects of the study through a total sampling technique. The research instrument was a validated flow scale that showed high reliability (Cronbach's Alpha= 0.930). The results showed that the majority of students (80%) were in the moderate flow category, 14% in the high category, and 6% in the low category. These findings highlight the importance of self-management strategies and environmental support in supporting the psychological well-being of students who play dual roles as academics and organizers.